IMPLEMENTASI SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) MELALUI APLIKASI KLIK PELALAWAN OLEH PEMERINTAH KABUPATEN PELALAWAN TAHUN 2022-2024 - Amelia, Risti; ., Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research discusses the implementation of the Electronic-Based Government System (SPBE) through the Klik Pelalawan Application by the Pelalawan Regency Government from 2022 to 2024. The issue addressed in this study is that the Klik Pelalawan application is still Android-based and many features remain inaccessible. The aim of this research is to understand the implementation of the Electronic-Based Government System (SPBE) through the Klik Pelalawan Application by the Pelalawan Regency Government in the years 2022–2024. This research uses a descriptive qualitative approach with interview and documentation techniques, and refers to the e-government implementation theory by Richardus Eko Indrajid (2002), which includes content development, competency development, connectivity, legal framework and instruments, collaboration, and project funding. The results of the study show that the implementation of the Klik Pelalawan application is underway but still not optimal. In terms of content development, the application has been well designed, but several issues remain. In terms of competency development, recruitment has been based on expertise, training has been provided, and appreciation has been given, although training remains insufficient. Regarding connectivity, the application was developed based on legal regulations concerning SPBE. As a result, a regent regulation was established to provide technical guidelines for the use of the Klik Pelalawan application and to ensure identity security. In terms of collaboration, the government has jointly operated the application, but socialization efforts remain lacking. Finally, in terms of project funding, there is no specific budget allocation designated for the application. Keywords: Klik Pelalawan Application, E-Government Implementation, SPBE